Brentuximab vedotin administered to platinum‐refractory, transplant‐naïve Hodgkin lymphoma patients can increase the proportion achieving FDG PET negative status. Issue 4 (18th September 2014) - Onishi, Maika; Graf, Solomon A.; Holmberg, Leona; Behnia, Sanaz; Shustov, Andrei R.; Schiavo, Karen; Philip, Mary; Libby, Edward N.; Cassaday, Ryan D.; Pagel, John M.; Roden, Jennifer E.; Maloney, David G.; et al.
Abstract: Normalization of fluorodeoxyglucose positron emission tomography (FDG PET) imaging prior to high‐dose therapy and autologous stem cell transplantation (ASCT) improves outcomes in relapsed and refractory (RR) Hodgkin lymphoma (HL), but many patients refractory to platinum‐based salvage regimens are unable to achieve this goal. We therefore investigated whether brentuximab vedotin (BV) could normalize FDG PET in platinum‐refractory HL prior to ASCT. Fifteen consecutive patients with RR HL and FDG PET positive disease after platinum‐based salvage therapy were treated with a median of 4 cycles of BV. Normalization of FDG PET (Deauville ≤2) occurred in 8/15 (53%) patients but was only observed in patients that had achieved partial remission or stable disease after platinum‐based salvage therapy. All patients eventually proceeded to ASCT, regardless of FDG PET status. Our data suggest that BV can normalize FDG PET in a subset of patients with platinum‐refractory HL prior to ASCT. Copyright © 2014 John Wiley & Sons, Ltd.